The franchise market and its economic, social and environmental contribution - Tassigny, Mônica Mota; Silva, Isadora Margarete Guimarães da; Brasil, Marcus Vinicius de Oliveira; Bizarria, Fabiana Pinto de Almeida; Frota, Antonio Jackson Alcantara (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Thestarting questionof this researchis how theBrazilian Franchising Association(ABF) has helpedin the economic,social and environmentalrequirements tothe developmentof the domestic market? Theobjective of this workis to analyzethe resultsof the actions ofeconomic, social and environmental responsibilityof the BrazilianFranchising Association(ABF) for thedevelopment of the Brazilianmarketfranchises. TheABFisa non-profitpurposesandconsolidatedin the market. Therefore, it isa theoreticalanddescriptive workbased onsecondary sources. The franchisesare representedby numbersfrom the same companythat has awider scopein the market,not to mentionthat ithasvisibilityto the publicconsumers, competitors, regulatory agenciesand activists. Allthese subjectsplay an importantrole, that ofinspection agentsofthese organizationsdiscloseinformationabout his conducttowards the environmentandsociety.